Plyometric training improves not only measures of linear speed, power, and change-of-direction speed but also repeated sprint ability in young female handball players - Chaabene, H.; Negra, Y.; Moran, J.; Prieske, O.; Sammoud, S.; Ramirez-Campillo, R.; Granacher, U. (The Journal of Strength and Conditioning Research, 2021)
This study examined the effects of an 8-week plyometric training (PT) program on components of physical fitness in young female handball players. Twenty-one female adolescent handball players were assigned to an experimental group (EG, n = 12; age = 15.9 ± 0.2 years) or an active control group (CG, n = 9, age = 15.9 ± 0.3 years). While EG performed plyometric exercises in replacement of some handball-specific drills, CG maintained the regular training schedule. Baseline and follow-up tests were performed for the assessment of linear speed (i.e., 5-, 10-, and 20-m time), change-of-direction (CoD) speed (i.e., T-test time), muscle power (i.e., countermovement jump [CMJ] height and reactive strength index [RSI]), and repeated sprint ability (RSA) (RSA total time [RSAtotal], RSA best time [RSAbest], and RSA fatigue index [RSAFI]). Data were analyzed using magnitude-based inferences. Within-group analyses for the EG revealed moderate-to-large improvements for the 5-m (effect size [ES] = 0.81 [0.1-1.5]), 10-m sprint time (ES = 0.84 [0.1-1.5]), RSI (ES = 0.75 [0.1-1.4]), RSAFI (ES = 0.65 [0.0-1.3]), and T-test time (ES = 1.46 [0.7-2.2]). Trivial-to-small ES was observed for RSAbest (ES = 0.18 [-0.5 to 0.9]), RSAtotal (ES = 0.45 [-0.2 to 1.1]), 20-m sprint time (ES = 0.56 [-0.1 to 1.2]), and CMJ height (ES = 0.57 [-0.1 to 1.3]). For the CG, within-group analyses showed a moderate performance decline for T-test time (ES = -0.71 [-1.5 to 0.1]), small decreases for 5-m sprint time (ES = -0.46 [-1.2 to 0.3]), and a trivial decline for 10-m (ES = -0.10 [-0.9 to 0.7]) and 20-m sprint times (ES = -0.16 [-0.9 to 0.6]), RSAtotal (ES = 0.0 [-0.8 to 0.8]), and RSAbest (ES = -0.20 [-0.9 to 0.6]). The control group achieved trivial-to-small improvements for CMJ height (ES = 0.10 [-0.68 to 0.87]) and RSI (ES = 0.30 [-0.5 to 1.1]). In conclusion, a short-term in-season PT program, in replacement of handball-specific drills, is effective in improving measures of physical fitness (i.e., linear/CoD speed, jumping, and RSA) in young female handball players.